PENGARUH LATIHAN PLYOMETRIC TERHADAP KECEPATAN TENDANGAN CHUDAN GERI PADA CABANG OLAHRAGA KARATE DOJO UNIVERSITAS PGRI PALEMBANG - Jujur Gunawan Manullang (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The problems of this study was the tehnique used to determine the exact performance and currently the athlete is kicking towards the target has not been right. To improve the results kick cheri gerry given plyometric exercise. The tthings that need to be done is to pply obstancle hurdles to speed of chudan geri movement. The result showed that the results of hypotesis testing obtained tcount = 4,061 and Ttabel =1,70. With the profit level like =5% or called 95%. Based on the calculation of criteria of the censusthta T.hitung >T.tabele =4,061>1,70 thus h0 is rejected and ha accepted. there is a significant effect on the hop hoist on the speed of the churi geri kick Keywords— plyometric, speed chudan geri kick